Can a Spirit of Our Own be Expressed in the Language of Our Coloniser? - Lahiri, Indian Institute of Technology, Gandhinagar, India, Sharmita (Asiatic: IIUM Journal of English Language and Literature, 2013)
This study explores the relationship between the concept of Indian identity and the English language as reflected in Indian literature. Questions of identity in this literature are inextricably connected with the issue of using English, the language of the erstwhile colonisers, to portray the non-English, multilingual socio-cultural and political experience of the Indian space. I argue that English is today an Indian language and even functions as a vernacular Indian language. An attempt to dismiss English as the language of the coloniser is endeavouring to reverse the wheels of history, because the Indian nation itself is a product of colonialism. Literature written in this language is not antithetical to or removed in its concerns from literature written in the different regional Indian languages. Rather, like literature in any other Indian language, not only is Indian-English literature credible Indian literature, but often it expresses a sensibility associated with the vernacular and can be meant primarily for an Indian audience. The vernacularisation of English is not based on any linguistic peculiarities of Indian English, but is achieved through the socio-political aspects of the language and the literary articulations of English in a mutually constitutive manner alongside various Indian regional languages.